1998
DOI: 10.1177/03635465980260031101
|View full text |Cite
|
Sign up to set email alerts
|

Articular Cartilage Changes Seen With Magnetic Resonance Imaging-Detected Bone Bruises Associated With Acute Anterior Cruciate Ligament Rupture

Abstract: Occult osteochondral lesions (bone bruises) have been documented on magnetic resonance images in more than 80% of patients sustaining acute anterior cruciate ligament ruptures. Despite the high prevalence of these lesions, little is known about the histologic changes in the adjacent articular cartilage. Ten patients with acute anterior cruciate ligament ruptures who had a preoperatively documented (by magnetic resonance imaging) geographic bone bruise at the sulcus terminalis on the lateral femoral condyle und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
196
0
10

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(215 citation statements)
references
References 21 publications
4
196
0
10
Order By: Relevance
“…1 The relationship of previous injury to the development of knee OA has been established by meta-analyses and case series [2][3][4] showing progressive cartilage loss or ''chondropenia'' 5 that may arise from compromised chondrocyte viability. [6][7][8] Strategies that prevent cartilage degeneration in the posttraumatic knee would be very valuable. Although there is experimental evidence that this goal may be attainable, [9][10][11][12][13][14][15] recent reviews of OA treatment strategies in clinical trials concluded that definitive evidence for disease modification in OA is scant.…”
mentioning
confidence: 99%
“…1 The relationship of previous injury to the development of knee OA has been established by meta-analyses and case series [2][3][4] showing progressive cartilage loss or ''chondropenia'' 5 that may arise from compromised chondrocyte viability. [6][7][8] Strategies that prevent cartilage degeneration in the posttraumatic knee would be very valuable. Although there is experimental evidence that this goal may be attainable, [9][10][11][12][13][14][15] recent reviews of OA treatment strategies in clinical trials concluded that definitive evidence for disease modification in OA is scant.…”
mentioning
confidence: 99%
“…Johnson et al found significant proteoglycan loss, chondrocyte injury and matrix degeneration in the articular cartilage adjacent to a geographic BML, as well as osteocyte necrosis within the affected bone marrow 32 . A separate follow-up study by Theologis et al found that the matrix composition in cartilage overlying bruises in the lateral tibia was still abnormal one year post-injury despite most of the original osteochondral lesions healing almost completely within 2 weeks to 6 months 18 .…”
Section: Post-traumatic Bone Marrow Lesionsmentioning
confidence: 99%
“…Direct cartilage damage is associated with short-term matrix disruption, chondrocyte necrosis and proteoglycan loss 32 . Though it is not yet known whether these changes are ultimately reversible, or become irreversible if a certain amount of damage is sustained, it is possible that the initial trauma plays a role in instigating the well-described progressive cartilage loss that is characteristic of osteoarthritis 18,32 .…”
Section: Direct Articular Cartilage Damagementioning
confidence: 99%
See 1 more Smart Citation
“…1 In cases of knee ligament injury, early detection of bone bruises is seen in over 80% of cases. 2,3 These lesions have also been observed in clinical cases without acute ligament or osteochondral damage. 4 Recently investigators 3,5 documented early degeneration of overlying articular cartilage and chondrocyte death with these bone lesions.…”
mentioning
confidence: 94%